Email: From Hero to Zero – the Beginning of the End?. Issue 2 (November 2015) - Silic, Mario; Back, Andrea; Silic, Dario
In 2011, the CEO of Atos, Thierry Breton, announced an unprecedented move for the company. The global information services giant would become a 'zero' email company with the objective of eradicating internal email use and replacing it with blueKiwi – enterprise social network software. This case serves to teach the challenges and key lessons behind the social collaboration transformation in a large organization where 76, 000 employees switched to a new mode of collaboration. The approach of how to become a zero email company is detailed, highlighting the importance of the first-order and second-order change. The case helps to understand what it takes to shift organizational culture and employee mindset, as well as what challenges and barriers need to be overcome to make such an important step on a large organizational scale.